2015
DOI: 10.3201/eid2111.141901
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus P[8] Infections in Persons with Secretor and Nonsecretor Phenotypes, Tunisia

Abstract: To determine whether rotavirus infections are linked to secretor status, we studied samples from children in Tunisia with gastroenteritis. We phenotyped saliva for human blood group antigens and tested feces for rotavirus. Rotavirus was detected in 32/114 patients. Secretor genotyping showed that P[8] rotavirus infected secretors and nonsecretors, and infection correlated with presence of Lewis antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Increasing evidence supports linkages between HBGA phenotypes and RV epidemiology, indicating that HBGAs play an important role in determining interspecies transmission and disease burden of RVs. For example, whereas P [6] and P [19] RVs in the P[II] genogroup only recognize H type 1 antigen in the absence of the Lewis fucose, P [4] and P [8] RVs require the Lewis b (Le b ) modified H type 1 antigens [19,25], supporting the observation that Leindividuals may have increased risk of P [6] RV infection whereas nonsecretors and Leindividuals may be resistant to P [4] and P [8] RV infections that require the Lewis and secretor fucose for host infection [26][27][28]. The P [9], P [14], and P [25] genotypes in the P[III] genogroup recognize type A HBGAs [9], which explains that P [14] infection in both humans and animals may due to type A HBGAs that are shared between human and animal species [9,18,29].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Increasing evidence supports linkages between HBGA phenotypes and RV epidemiology, indicating that HBGAs play an important role in determining interspecies transmission and disease burden of RVs. For example, whereas P [6] and P [19] RVs in the P[II] genogroup only recognize H type 1 antigen in the absence of the Lewis fucose, P [4] and P [8] RVs require the Lewis b (Le b ) modified H type 1 antigens [19,25], supporting the observation that Leindividuals may have increased risk of P [6] RV infection whereas nonsecretors and Leindividuals may be resistant to P [4] and P [8] RV infections that require the Lewis and secretor fucose for host infection [26][27][28]. The P [9], P [14], and P [25] genotypes in the P[III] genogroup recognize type A HBGAs [9], which explains that P [14] infection in both humans and animals may due to type A HBGAs that are shared between human and animal species [9,18,29].…”
Section: Introductionmentioning
confidence: 87%
“…The discovery that P [4], P [6], and P [8] human RVs recognize the secretor epitopes of human HBGAs appears to correlated with the predominance of these genotypes in causing the vast majority (>95%) of human infections worldwide. Epidemiological and biochemical studies suggest that non-secretors and Leindividuals may be resistant to P [4] and P [8] infections [27,28,56,57]. Nonsecretors are also possible to be susceptible to infection with prevalent human RVs as other epidemiological study demonstrated no significant correlation was found between secretor status and the susceptibility to P [6] RV infections [26].…”
Section: Our Data Also Provide Clues About the Evolution Of P[ii] Rvsmentioning
confidence: 96%
“…In Burkina Faso, no Lewis-negative secretors (expressing H type 1 antigen) were infected with P[8] strains, despite making up 25% of the study population [78], suggesting that the infectivity of P[8] strains may be dependent on both secretor and Lewis status. However, population-specific differences may exist; for example, P[8] infections were detected in both secretors and nonsecretors during a study in Tunisia [79].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…In Burkina Faso, no Lewis-negative secretors (expressing H type 1 antigen) were infected with P[8] strains, despite making up 25% of the study population [78], suggesting that the infectivity of P[8] strains may be dependent on both secretor and Lewis status. However, population-specific differences may exist; for example, P[8] infections were detected in both secretors and nonsecretors during a study in Tunisia [79].In addition to being among the globally dominant rotavirus genotypes, P[8] strains are a component of Rotarix and RotaTeq. It is therefore plausible that genotype-specific HBGA binding patterns may contribute to geographic differences in vaccine efficacy.…”
mentioning
confidence: 99%
“…For instance, loss of FUT2 function leads to virtually no infection with P [8] strains in countries like Vietnam 19 and the USA, 20 but not in Tunisia where among 32 children infected, P [8] was present in both secretor and non-secretors that are positive for Lewis antigen. 21 Also, in Pakistan, a study comprising 181 infants that were seronegative before immunization with three courses of a G1P [8] vaccine strain indicated that 19% (10/ 54) of responders were non-secretors whereas secretors were 51% (20/39) type O and 30% (26/88) were types A, B or AB. 22 In addition, 18 P [6] infections (from a total of 27) were seen in predominantly Lewis-negative children (a frequent phenotype in African populations), while 27 Lewis-negative individuals were resistant to P [8] infection (0 in a total of 27 children).…”
Section: Rotavirus Disease Biology and Impactmentioning
confidence: 99%